2010
DOI: 10.1136/bjo.2010.187344
|View full text |Cite
|
Sign up to set email alerts
|

Short wavelength fundus autofluorescence versus near-infrared fundus autofluorescence, with microperimetric correspondence, in patients with geographic atrophy due to age-related macular degeneration

Abstract: Standard SW-FAF may overestimate GA in the foveal area, correctly detected by NIR-FAF. In the extrafoveal area, SW-FAF may underestimate GA. Standard SW-FAF should be integrated with NIR FAF when detecting and following GA to avoid inconsistent results and misinterpretation, from both a morphological and functional perspective. Microperimetry helps to quantify retinal sensitivity in GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 20 publications
5
51
0
Order By: Relevance
“…However, in highly elevated tumors, artifacts related to the technique may limit the analysis [ 15 ]. It has been suggested that longer and deeper wavelengths, such as NIR, could provide more information about the pigment composition of choroidal melanocytic lesions [ 3 ]. With NIR-AF, the melanin distribution can be explored, as oxidized melanin or compounds closely associated with melanin.…”
Section: Choroidal Melanomamentioning
confidence: 99%
See 3 more Smart Citations
“…However, in highly elevated tumors, artifacts related to the technique may limit the analysis [ 15 ]. It has been suggested that longer and deeper wavelengths, such as NIR, could provide more information about the pigment composition of choroidal melanocytic lesions [ 3 ]. With NIR-AF, the melanin distribution can be explored, as oxidized melanin or compounds closely associated with melanin.…”
Section: Choroidal Melanomamentioning
confidence: 99%
“…Above the age of 70, as much as 20 % of the free cytoplasmic space of the RPE cells is occupied by LF granules but also by melanolipofuscin granules (MLF), a compound product of LF and melanin [ 2 ]. Also MLF acts as a fl uorophore, needing specifi c wavelengths of excitation and cutoff fi lters for emitting light (different from LF) to obtain the MLFrelated emission peak [ 3 ]. MLF is present in RPE in physiologic conditions, but increases in different pathologic conditions as well as LF.…”
Section: The Origin Of Autofl Uorescencementioning
confidence: 99%
See 2 more Smart Citations
“…For accurate calculation of juxtafoveal geographic atrophy, NI-AF should be performed in conjunction with BL-AF imaging to avoid artefactual overestimation of the area of RPE cell loss when BL-AF is used alone. 14 The Heidelberg retina angiography (HRA) and HRA2 (Heidelberg Engineering, Heidelberg, Germany) were the first commercial devices used for the acquisition of BL-AF and NI-AF. 12Y14 However, these devices are now superseded by Spectralis HRA + OCT (Heidelberg Engineering) in most clinics.…”
mentioning
confidence: 99%